Assistance in Book-keeping and Capital Training for the Sari Rasa Bolong Home Industry Group, Banjar Pekandelan, Desa Adat Sading, Mengwi, Badung - Sudarmini, Ketut; Sugiati, Gusti Ayu; Pertiwi, I Dewa Ayu Eka (PT FORMOSA CENDEKIA GLOBAL, 2024)
Desa Adat Sading in Mengwi District has nearly 12% (873 people) of its population engaged in trade and home industries. The Jaje Bolong Sari Rasa Bolong group struggles to meet high customer demands due to limited equipment and insufficient capital. They market products via social media, and although sales are increasing, there is competition in pricing among similar producers. The group produces 15 kg of rice daily, all of which is sold locally. To reduce costs, they need a flour processing machine. Assistance was provided in book-keeping, determining cost of goods sold, and capital management. The group received a flour processing machine and was connected with a cooperative for working capital loans.